The Influence of Seismic Parameters on Site Response - Adel Asakereh; Hasan Jamali; E. Naderi (Institute of Research and Community Outreach - Petra Christian University, 2015)
Geotechnical earthquake engineers have been trying to determine the most appropriate solution techniques for ground response analysis under earthquake loadings. This paper presents the importance of the adequate soil behavior model to simulate earthquake site response analysis. The influence of nonlinearity and linearity of soils on the site response is also investigated. Many methods have been proposed for the analysis of one-dimensional ground response such as nonlinear methods and equivalent linear with reduced modulus. Using 13 well known earthquake records and geotechnical information of sand in the Qeshm Island (Iran) and classification of earthquakes based on seismic parameters, the influence of each parameter on the Response spectra and Fourier Spectrum of surface of ground becomes evident. Analysis was done using two softwares; EERA (equivalent linear analysis) and NERA (nonlinear analysis) and compared. Finally, output of the software is compared with the reference result on site.